Causal associations between osteoporosis and HBV infection across Asian and European populations: evidence from Mendelian randomization and colocalization analysis - Li, Zhengnan; Cao, Jiarui; Li, Ke; Wu, Yixin; Luo, Zhanpeng; Cao, Rui; Cheng, Zhiheng; Tian, Zhendong; Han, Yiyang; Lai, Yuping; Wang, Bangqi; Chen, Shen (Frontiers in Endocrinology, 2025)
IntroductionClinical studies have demonstrated a potential association between chronic hepatitis caused by hepatitis B virus (HBV) infection and osteoporosis. However, the causal relationship between HBV infection and osteoporosis remains to be determined.MethodsWe investigated whether HBV infection is causally associated with osteoporosis using Mendelian randomization (MR) in East Asian and European populations, respectively. The data we utilized were obtained from the genome-wide association studies (GWAS) database. Various MR methods, including inverse variance weighted (IVW), MR Egger, weighted median, simple median and simple mode were employed to estimate the association between HBV infection and osteoporosis. Heterogeneity analysis and sensitivity tests were performed to ensure the robustness of the results. Bayesian co-localization (coloc) analysis was also applied to calculate the posterior probability of causal variants and to identify common genetic variants between HBV infection and osteoporosis.ResultsMR analysis indicated that HBV infection increased the risk of osteoporosis onset in two East Asian cohort (IVW, OR = 1.058, 95% CI = 1.021 to 1.097, P = 0.002 and OR = 1.067, 95% CI = 1.029 to 1.106, P < 0.001). However, a clear effect of genetic susceptibility to HBV on the enhanced risk of osteoporosis was not observed in two European cohort (IVW, OR = 1.000, 95% CI = 0.999 to 1.001, P = 0.171 and OR = 1.003, 95% CI = 0.981 to 1.025, P = 0.780). Additional MR methods and sensitivity analyses further validated the reliability and robustness of our results. Bayesian co-localization analysis revealed co-localization of HBV infection and osteoporosis on STAT4 at rs11889341based on East Asian GWAS data.ConclusionsOur study identified a causal relationship between HBV infection and osteoporosis in East Asian and European populations. These results provided strong evidence that HBV infection augmented the risk of developing osteoporosis in East Asian populations and provided novel therapeutic targets.